An Approach for controlling Household Electrical devices using Bluetooth communication system via Smartphone devices - Mohammed Babban, Miran Hikmat (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Technologies software applications and hardware devices in general play a big role in everything in our life, which make things to be done quickly and easily comparing to some few years ago. Even though, these rapid developments in technologies comprises electrical devices that we are use in daily manner as well. In this research, an idea is applied to provide a smart house technology which can control any electrical for any domestic device in households, this is done by using Bluetooth networking connection through using mobile smartphone. The main goal of this research is to show that there are possibilities to control any electrical devices in home via controlling them remotely and at any time and at anywhere around the home. So, it provides easy accessibility to switch on or off devices, also it delivers safety use of those electrical devices.